Kidney Transplantation From Deceased Donors With Vaccine-induced Immune Thrombocytopenia and Thrombosis: An Updated Analysis of the UK Experience. Issue 9 (13th July 2022) - Greenhall, George H.B.; Ushiro-Lumb, Ines; Pavord, Sue; Hunt, Beverley J.; Sharma, Hemant; Mehra, Sanjay; Calder, Francis; Kessaris, Nicos; Kilbride, Hannah; Jones, Gareth; Motallebzadeh, Reza; Arslan, Zainab; et al.
Abstract : Background: The emergence and attendant mortality of vaccine-induced immune thrombocytopenia and thrombosis (VITT) as a consequence of vaccination against severe acute respiratory syndrome coronavirus 2 have resulted in some patients with VITT being considered as deceased organ donors. Outcomes after kidney transplantation in this context are poorly described. Because the disease seems to be mediated by antiplatelet factor 4 antibodies, there is a theoretical risk of transmission via passenger leukocytes within the allograft. Methods: We analyzed the experience of kidney transplantation from donors with VITT in the United Kingdom between January and June 2021. We followed-up all recipients of kidney-only transplants from donors with VITT to detect major postoperative complications or features of disease transmission and assess graft survival and function. Results: There were 16 kidney donors and 30 single kidney transplant recipients in our study period. Of 11 preimplantation biopsies, 4 showed widespread glomerular microthrombi. After a median of 5 mo, patient and graft survival were 97% and 90%, respectively. The median 3-mo estimated glomerular filtration rate was 51 mL/min/1.73 m 2 . Two recipients had detectable antiplatelet factor 4 antibodies but no evidence of clinical disease after transplantation. Major hemorrhagic complications occurred in 3 recipients, all of whom had independent risk factors for bleeding, resulting in the loss of 2 grafts. The involvement of VITT could not be completely excluded in one of these cases. Conclusions: The UK experience to date shows that favorable outcomes are possible after kidney transplantation from donors with VITT but highlights the need for ongoing vigilance for donor-related complications in these patients.